(untitled) (GIST – Education and Learning Research Journal, 2020)
Adjective- noun order errors are a common occurrence throughout all levels of English language students. Based on professional experiences, existing literature and revisiting what some may consider archaic methodologies, this reflective article aims to analyse adjective-noun order errors among Colombian learners of English, understand why it presents such a challenge in the Colombian context and provide one possible teaching method to help reduce the number of adjective-noun order errors produced. To achieve such aims this article compares the rules for adjective-noun order in English and Spanish, describes the implications of the differences in adjective-noun order between the two languages for the Colombian learner and proposes translation as a teaching method to help Colombian learners of English reduce the frequency of these errors. Further investigation is needed to provide teachers with more insight into this problem; perhaps, focussing specifically on one of the two skills in which the error is produced, either writing or speaking.